Proposta metodológica para estimação de ganhos em projetos de controle e automação - Fabio Barros de Carvalho (2010)
A methodology for estimating project benefits is proposed as a strategy to analyse the investments of a company. The methodology is focused on control and automation projects and extends some concepts and leading practices present on the literature. Its implementation supports the portfolio selection task using the potential return of each endeavour as a decision factor. The method is composed by six major steps startingfrom an understanding of the project scope together with the company business objectives, passing through an analysis of the historical behavior of the productive process and ending with the calculation of the projects potential benefits. Multivariate statistical analysis techniques like PLS, variability matrix and cross correlation are incorporated on the methodology. Three case studies are conducted over real data,process and projects in order to demonstrate the applicability of the proposed method.